Osmotic dehydration of banana fruit slices using honey as osmotic solution - Mohd Kamarul 'Aripin Kasmori (2011)
The osmotic dehydration process is one of the established methods for preserving fresh produces in food industry. The idea of using honey as an alternative source of osmotic solution in the osmotic dehydration process is determined to be used in this study. The use of honey is good to preserve banana fruit for better dehydrated end products in food industry. The result from this study is the osmotic dehydrated banana was determined to have a water loss up to 22% (wet basis) after osmotic dehydration process using honey as osmotic solution. The solute gain in the sample was determined that shows negative results in average of -0.19 gram per sample. The shrinkage of the banana samples is high up to 62% of the original sample. The appearance of osmotic dehydrated banana is acceptable by the consumer panels as a good quality product through the minimum changes from the original sample. The design the experiment is using Response Surface Method (RSM) by applying Central Composite Design (CCD). There are some factors used to determine the optimum condition of osmotic dehydration process in this study such as water loss of the sample, solute gain toward the sample, the evaluation of sample's appearance and the shrinkage of the sample. The optimum condition for the osmotic dehydration process determined from this study is 55°C of temperature and 5 hour immersion time that is the suitable condition obtained from this study.